10‐Hydroxy‐2‐decenoic acid, a unique medium‐chain fatty acid, activates 5'‐AMP‐activated protein kinase in L6 myotubes and mice. Issue 10 (10th June 2013) - Takikawa, Masathito; Kumagai, Aya; Hirata, Harumi; Soga, Minoru; Yamashita, Yoko; Ueda, Manabu; Ashida, Hitoshi; Tsuda, Takanori
<x xml:space="preserve">Abstract</x> Scope 10‐Hydroxy‐2‐decenoic acid (10H2DA) is one of the unique medium‐chain fatty acids (MCFAs) specifically found in royal jelly. We hypothesize that 10H2DA has multiple biological functions and may aid in 5′‐AMP‐activated protein kinase (AMPK) activation and affect the glucose transport system in skeletal muscle. Methods and results We examined whether various MCFAs present in royal jelly activated AMPKα. Treatment of L6 myotubes with various MCFAs showed that 10H2DA administration resulted in a significant increase in phosphorylated AMPKα. 10H2DA activates AMPK independently of insulin and significantly increased glucose uptake into L6 myotubes following translocation of glucose transporter 4 (Glut4) to the plasma membrane (PM). The activation was induced by the upstream kinase Ca2+/calmodulin‐dependent kinase kinase β, but was independent of changes in AMP:ATP ratio and the liver kinase B1 pathway. Oral administration of 10H2DA significantly stimulated phosphorylation of AMPK and Glut4 translocation to the PM in mouse skeletal muscle. Conclusion These findings indicate that (i) 10H2DA activates AMPK, and insulin independently enhances glucose uptake following translocation of Glut4 to PM, (ii) activation of AMPKα by 10H2DA is mediated via extracellular Ca2+‐dependent Ca2+/calmodulin‐dependent kinase kinase β, without alteration in the AMP:ATP ratio, and liver kinase B1 was not involved in the activation.